Senegal : Selected Issues. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2015)
This Selected Issues paper on Senegal revisits the challenges of emergence by tapping on the experience of other countries across the world that became emerging economies in the past two decades. It then looks at the preconditions needed for growth acceleration in Senegal. The paper also discusses options for strengthening Senegal's fiscal framework to support Plan Senegal Emergent (PSE) implementation while keeping risks of debt distress low. It provides an assessment of Senegal's external stability and explores how to improve the structure of the Senegalese economy to make it more competitive with more diversified exports. The paper describes the electricity problem as a major impediment to growth acceleration. Improved revenue performance and expenditure composition are critical for creating the fiscal space to support the PSE. There is an opportunity cost for development spending, as the economy still faces bottlenecks from high electricity costs and insufficient electricity production. The share of the population living below the poverty line and its exposure to shock remains unacceptably high.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet